The issue of Rejection of Positivist and Materialist Reflections in Turkish Thought - Aba Müslim Akdemir (Felsefe Dünyası)
The influence of the adventure of modernization on the reflections ofpositivist philosophy and materialist philosophy on our tradition of thoughtcannot be ignored. In this process, French scientific and philosophical circleshad a central influence on our culture through copyrighted and translatedworks. In addition, German philosophy was introduced through whatthe Ottoman intelligentsia read in French. Especially the positivist, materialist,and naturalistic influences created an environment of polarizationwhere the supporters of traditionalism faced off against those of modernityat the triangle of religion, science, and philosophy. Based on their positivistand materialist thoughts, thinkers such as Beşir Fuat, Abdullah Cevdet,Celal Nuri, Baha Tevfik, and Ahmed Nebil, who were the supporters of thetradition of modernization, grounded their arguments on religion, science,and philosophy, the achilles’ heel of traditionalists. Against them stoodrejectionists such as Fatma Aliye, İsmail Ferit, Harputizade Hacı Mustafa,Filibeli Ahmet Hilmi, Emin Feyzi, Mehmet Ali Ayni, and İsmail Fenni,who were against the positivist and materialist influences and groundedtheir arguments on spiritualist philosophy, idealist philosophy, Bergson’sphilosophy, and action philosophy. However, it can be said that in the issueof rejection, religious and sufistic traditions came to the forefront ratherthan a philosophical opposition.